Dielectric dispersion of laminated dielectrics; Proceedings of 3th International Conference on Electric Charge in Solid Insulation (CSC'3) (Tours, France, 29 June-3 July, 1998) - Lebedev S.M.; Gefle O.S.; Chichikin V.I.; Pokholkov Y. P. Yuri Petrovich (1998, 1998)
В фонде НТБ ТПУ отсутствует